Reemerging Rice Orange Leaf Phytoplasma with Varying Symptoms Expressions and Its Transmission by a New Leafhopper Vector—Nephotettix virescens Distant - Jonson, Gilda B.; Matres, Jerlie M.; Ong, Socheath; Tanaka, Toshiharu; Choi, Il-Ryong; Chiba, Sotaro (Pathogens (Basel), 2020)
Rice orange leaf phytoplasma (ROLP) belongs to the “Candidatus Phytoplasma asteris” 16SrI-B subgroup, which is solely transmitted by the zigzag-striped leafhopper (Recilia dorsalis Motchulsky) and the green leafhopper (Nephotettix cincticeps Uhler) (Hemiptera: Cicadellidae). Recently, rice plants showing orange leaf discoloration have become ubiquitous in several paddies of two provinces in the Philippines. In total of 98 symptomatic rice plants, 82% (Laguna) and 95% (Mindanao) were ROLP-positive by nested PCR detection. These plants showed more varying symptoms than previously reported. The vector insect R. dorsalis was scarcely present but green paddy leafhopper, N. virescens Distant (Hemiptera: Cicadellidae), was commonly observed in the paddies, thus the ability of N. virescens to transmit ROLP was thoroughly investigated. Newly emerged adult N. virescens, which fed on ROLD-source rice plants, were used to inoculate a susceptible rice seedling and was serially transferred into a new healthy seedling. Resultant positive transmission rates varied from 5.1% to 17.8%. The transmission ability of the insects was generally decreased over time. These findings suggest that N. virescens is an alternative vector of ROLP in the Philippines. Altogether, this study highlighted the increasing importance of ROLD-reemergence in Southeast and East Asia and proved the need for careful management of this alternative vector insect.